Teachers’ challenges affecting the implementation of the new business subjects’ curriculum in selected secondary schools in Uganda - Muhwezi, Innocent (Journal of Management and Business Education, 2023)
The study aimed at identifying the teacher challenges that affect Business Subjects teachers’ preparedness in the implementation of the new Business Subjects curriculum in selected secondary schools of Kabale district, Uganda. Based on the pragmatist perspective, a concurrent triangulation research design was adopted. Data were collected from 37 business subject teachers and 13 directors of studies across 13 secondary schools in Kabale district, making a total of 50 participants. Semi-structured interview schedules and closed questionnaires were used for data collection. Quantitative data were analysed using descriptive statistics while qualitative data were analysed using a thematic analysis approach. Findings indicated that teacher challenges that affected the implementation of the new Business subject’s curriculum included: lack of adequate teacher in-service training; limited competent human resources among others. The quantitative findings as Business Subjects indicated that they were being faced with both inside and outside school challenges while in the implementation of the new Business Subjects curriculum This denoted also a high percentage of over 67% that was posted by all the items that were used to measure teacher challenges that affected Business Subjects teachers’ preparedness for the implementation of the new Business Subjects curriculum in both private and public secondary schools.